TEORI PENDIDIKAN SEUMUR HIDUP DAN PENDIDIKAN UNTUK SEMUA - Hakim, Azizul (Jurnal Pendidikan Kreatif, 2020)
This paper discusses educational theory. Education includes a comprehensive scope, namely the education of mental abilities, thinking, and human personality as a whole. Education of course applies to all humans without exception. Education actually does not only take place in schools. Education will start as soon as the child is born and will continue until the human dies. Education takes place in families, schools and communities. In this paper, the authors focus on discussing the theory of lifelong education and education for all. Knowing this material is important because education is an absolute necessity for human life that must be fulfilled throughout life. The main problems that the authors discuss in this paper are the theory of life-long education and education for all, the legal basis and the rationale that underlie the importance of lifelong education and education for all, and their implications in educational programs.The conclusion of this paper is that life-long education formulates a principle that the educational process is a process that must be carried out continuously, starting from birth to death and includes informal, non-formal and formal forms of learning. The rationale for the importance of lifelong education can be viewed from various aspects, including ideological, economic, sociological, technological, psychological, pedagogical, and philosophical aspects. The implications of the concept of lifelong education can be seen from several aspects related to "learning methods" and "educational models".